1995
DOI: 10.1007/bf00854981
|View full text |Cite
|
Sign up to set email alerts
|

Phonomyogram from single motor units during voluntary isometric contraction

Abstract: The purpose of this study was to determine the characteristics of the specific phonomyogram (PMG) of active motor units activated during voluntary isometric contractions. The electromyogram (EMG) and PMG were recorded from 87 anconeus motor units in 14 subjects. The elementary PMG from single motor units was analysed with a spike-triggered averaging technique. The electro-acoustical delay was 3.5 (SD 1.1) ms, which is within the range of values reported in the literature for PMG evoked by motor nerve stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 29 publications
1
42
1
Order By: Relevance
“…The size of the air chamber is considered to have an effect on the MMG recording. Previous investigations employed different cylinder sizes ranging in length from 1 to 15 mm, although the diameters were similar (BOLTON et al, 1989;GOLDENBERG et al, 1991;PETITJEAN and BELLEMARE, 1994;PETITJEAN and MATON, 1995;CHEN et al, 1997;CELICHOWSKI et al, 1998;COURTEVlLLE et al, 1998). However, the optimal air chamber for the MMG measurement is still undetermined.…”
Section: Introductionmentioning
confidence: 95%
“…The size of the air chamber is considered to have an effect on the MMG recording. Previous investigations employed different cylinder sizes ranging in length from 1 to 15 mm, although the diameters were similar (BOLTON et al, 1989;GOLDENBERG et al, 1991;PETITJEAN and BELLEMARE, 1994;PETITJEAN and MATON, 1995;CHEN et al, 1997;CELICHOWSKI et al, 1998;COURTEVlLLE et al, 1998). However, the optimal air chamber for the MMG measurement is still undetermined.…”
Section: Introductionmentioning
confidence: 95%
“…2 Most previous studies have examined MMG responses during isometric muscle actions. 27,29,35,45 A recent investigation by Dalton and Stokes,12 however, reported a positive, linear relationship between MMG amplitude and force during dynamic submaximal concentric (r 2 = 0.88) and eccentric (r 2 = 0.81) muscle actions of the biceps brachii. Petitjean et al 30 also reported a linear relationship for the MMG amplitude-force relationship (r 2 = 0.85) for the biceps brachii and greater MMG amplitude during fast than slow movements.…”
mentioning
confidence: 94%
“…In the case of the MMG from a single motor unit, transducers attached to the skin have been used. As contact type transducers, microphones [13], piezoelectric sensors [14], and acceleration sensors [15] have all been previously used. An acceleration sensor is the smallest and lightest sensor among them.…”
Section: Discussionmentioning
confidence: 99%